Kinerja dan Kecerdasan Karyawan : Peran Kecerdasan Dalam Meningkatkan Kinerja Karyawan di Era Digital - akbar, moh rafi (Maliki Interdisciplinary Journal, 2025)
This study examines the role of emotional and intellectual intelligence in improving employee performance in the digital era. Individual intelligence is key to adapting to rapid technological change. Digital-based human resource strategies, such as the use of AI and information systems, contribute to increased efficiency and productivity. By understanding the importance of integrating emotional, intellectual, and digital competencies, organizations can build a responsive and innovative work environment that enhances overall employee loyalty and performance.